THE MANAGEMENT OF COMMUNITY EDUCATION IN RURAL AREA BY RELIGIOUS EDUCATION INSTITUTIONS - Mohammad Mustari (TEMALI : Jurnal Pembangunan Sosial, 2020)
This article discusses how public education institutions such as boarding schools face the social changes brought about by modernity. The assumption is that as agents of change, of course pesantren must follow what and how modernity itself can only provide answers to society. What is mainly brought about by modernity itself is development. Therefore, social change that must be answered primarily by pesantren is a matter of development. This study found that operationally, the relationship between pesantren and rural community development, which aspires to improve the quality of human resources in the pesantren, has been carried out through the following activities: consolidation and cooperation, business links and education, and insights into the pesantren's struggle, community, and the government.